Strategi Pendidikan Kedamaian pada Sekolah di Indonesia - Sahril Buchori -; Nurfitriany Fakhri (ILIN Institute Makassar, 2022)
A culture of peace is needed in various aspects of life, including in the world of education. This research presents a systematic scoping review study from publications that focuses on peace education strategies in schools in Indonesia. For this reason, 7 selected empirical studies from 146 publications originating from the Google Scholar database, according to inclusion and exclusion criteria, to address the interrelationships of the main themes summarized in the following three research questions: (i) what is the concept of peace to be achieved by schools in implementing peace education? (ii) what strategies are used by schools in developing peace education? and (iii) which parties are involved in implementing the peace education strategy in schools? The results of the research show that peace education can be implemented at various levels of education. The three main goals to be achieved by schools through peace education are: (1) education and character development that is peaceful and able to understand differences, (2) maintain social harmony, and (3) minimizing violent behavior. The third result is the peace education strategy carried out by schools, in outline integrated in the form of curriculum, learning processes, improving student welfare, student social relations, school facilities, as well as collaboration with all parties.